Political Alignment and Bureaucratic Pay - Jon H. Fiva; Benny Geys; Tom-Reiel Heggedal; Rune Jorgen Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the private gains to bureaucrats from their political alignment with elected politicians. Whereas existing studies generally rely on proxies for politician-bureaucrat political alignment, a rare feature of our data allows measuring it directly since 27% of bureaucrats ran for political office. We focus explicitly on individuals at the very top of the administrative hierarchy, and are able to separate the intensive margin (i.e. wage increases) from any additional effects at the extensive margin (i.e. new appointments). Using close elections for inference, we find that politician-bureaucrat alignment significantly increases top bureaucrats' wage even in the Norwegian civil service system. Our results go against predictions from models with policy-motivated bureaucrats, but are consistent with politically aligned principal-agent matches being more productive.
Keywords: D73; H70; J41; 330; bureaucracy; civil service; remuneration; principal-agent; ally principle